2022
DOI: 10.3390/ijms23116211
|View full text |Cite
|
Sign up to set email alerts
|

Ovulation Enhances Intraperitoneal and Ovarian Seedings of High-Grade Serous Carcinoma Cells Originating from the Fallopian Tube: Confirmation in a Bursa-Free Mouse Xenograft Model

Abstract: Background: Recently, new paradigms for the etiology and origin of ovarian high-grade serous carcinoma (HGSC) have emerged. The carcinogens released during ovulation transform fallopian tube epithelial cells, exfoliating and metastasizing to the peritoneal organs, including the ovaries. Solid in vivo evidence of the paradigms in a mouse model is urgently needed but is hampered by the differing tubo-ovarian structures. In mice, there is a bursa structure surrounding the distal oviduct and ovary. This, on one ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…In addition to the mutagenic effect, FF enhanced the full course of FTE transformation 24,25 . A broad spectrum of cell transformation phenotypes, such as stemness, clonal expansion, anchorage‐independent growth (AIG), migration, invasion, anoikis resistance, and peritoneal attachment, were all found to be enhanced by FF 24,26 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the mutagenic effect, FF enhanced the full course of FTE transformation 24,25 . A broad spectrum of cell transformation phenotypes, such as stemness, clonal expansion, anchorage‐independent growth (AIG), migration, invasion, anoikis resistance, and peritoneal attachment, were all found to be enhanced by FF 24,26 .…”
Section: Introductionmentioning
confidence: 99%
“…23 In addition to the mutagenic effect, FF enhanced the full course of FTE transformation. 24,25 A broad spectrum of cell transformation phenotypes, such as stemness, clonal expansion, anchorageindependent growth (AIG), migration, invasion, anoikis resistance, and peritoneal attachment, were all found to be enhanced by FF. 24,26 Besides the ROS, we have identified insulin-like growth factor (IGF2) and hepatocyte growth factor (HGF) as the essential oncogenic growth factors in FF.…”
Section: Introductionmentioning
confidence: 99%
“…xenograft tumorigenesis mouse experiment where, compared to the pro-tumorigenic effect of normal ovulation, superovulation did not increase the severity of the intraperitoneal seeding of high-grade serous carcinoma cells. 32 The same study also showed that the bursa-removed ovary ovulated normally and readily released FF to enhance tumor growth, thus clarifying whether bursectomy would compromise ovulation function. 32 Meanwhile, we also, chose ovariectomy surgery in the i.p.…”
Section: Discussionmentioning
confidence: 90%
“… 32 The same study also showed that the bursa-removed ovary ovulated normally and readily released FF to enhance tumor growth, thus clarifying whether bursectomy would compromise ovulation function. 32 Meanwhile, we also, chose ovariectomy surgery in the i.p. FF injection mouse model to avoid the disturbance of endogenous ovulation and specifically examine the effect of exogenous FF exposure on wound healing.…”
Section: Discussionmentioning
confidence: 90%
“…Molecular biology is characterized by TP53 mutations in almost all cases, resulting in high rates of genomic and chromosomal instabilities during carcinogenesis. Several lines of evidence now indicate that these tumors may originate from the epithelium of the fimbrial portion of the fallopian tube and/or the ovarian surface epithelium [18][19][20][21]. Uterine serous carcinoma (USC) is an overlooked component of breast cancer susceptibility gene 1/2 (BRCA1/2)-associated hereditary breast and ovarian cancer (HBOC) syndrome.…”
Section: Introductionmentioning
confidence: 99%